Pain Processing in a Social Context and the Link with Psychopathic Personality Traits—An Event-Related Potential Study - van Heck, Casper H.; Driessen, Josi M. A.; Amato, Maria; van den Berg, Marnou N.; Bhandari, Pritha; Bilbao-Broch, Laura; Farres-Casals, Jordi; Hendriks, Manon; Jodzio, Adrian C.; Luque-Ballesteros, Laura; Schöchl, Christina; Velasco-Angeles, Laura R.; et al. (Frontiers in Behavioral Neuroscience, 2017)
Empathy describes the ability to understand another person’s feelings. Psychopathy is a disorder that is characterized by a lack of empathy. Therefore, empathy and psychopathy are interesting traits to investigate with respect to experiencing and observing pain. The present study aimed to investigate pain empathy and pain sensitivity by measuring event-related potentials (ERPs) extracted from the ongoing EEG in an interactive setup. Each participant fulfilled subsequently the role of ‘villain’ and ‘victim’. In addition, mode of control was modulated resulting in four different conditions; passive villain, active villain, active victim and passive victim. Response-, visual- and pain ERPs were compared between all four conditions. Furthermore, the role of psychopathic traits in these outcomes was investigated. Our findings suggested that people experience more conflict when hurting someone else than hurting themselves. Furthermore, our results indicated that self-controlled pain was experienced as more painful than uncontrolled pain. People that scored high on psychopathic traits seemed to process and attend to pain differently. According to the results of the current study, social context and personality traits seem to modulate pain processing and the empathic response to pain in self and others. The within-subject experimental design described here provides an excellent approach to further unravel the influence of personality traits on social cognition.